Age-differential sexual dimorphism in CHD8-S62X-mutant mouse behaviors - Lee, Soo Yeon; Kweon, Hanseul; Kang, Hyojin; Kim, Eunjoon (Frontiers in Molecular Neuroscience, 2022)
Autism spectrum disorders (ASD) are ~4-times more common in males than females, and CHD8 (a chromatin remodeler)-related ASD shows a strong male bias (~4:1), although the underlying mechanism remains unclear. Chd8-mutant mice with a C-terminal protein-truncating mutation (N2373K) display male-preponderant behavioral deficits as juveniles and adults, although whether this also applies to other Chd8 mutations remains unknown. In addition, it remains unclear whether sexually dimorphic phenotypes in Chd8-mutant mice are differentially observed in males and females across different ages. We here generated new Chd8-mutant (knock-in) mice carrying a patient-derived mutation causing an N-terminal and stronger protein truncation (Chd8+/S62X mice) and characterized the mice by behavioral analyses. Juvenile Chd8+/S62X mice displayed male-preponderant autistic-like behaviors; hypoactivity and enhanced mother-seeking/attachment behavior in males but not in females. Adult male and female Chd8+/S62X mice showed largely similar deficits in repetitive and anxiety-like behavioral domains. Therefore, the CHD8-S62X mutation induces ASD-like behaviors in juvenile male mice and adult male and female mice, pointing to an age-differential sexual dimorphism and also distinct sexual dimorphisms in different Chd8 mutations (N2373K and S62X).